BAGAIMANA STRUKTUR MODAL, PROFITABILITAS DAN KEBIJAKAN DEVIDEN MEMPENGARUHI NILAI PERUSAHAAN ? (STUDI KASUS PT UNILEVER INDONESIA TBK) - Alifah Sajidah; Sunita Dasman (STKIP Subang, 2024)
Business competition in Indonesia is very tight, which makes companies display the best values ​​from the companies they lead. The aim of this research is to analyze the influence of capital structure, profitability and dividend policy on company value. The research was conducted at consumer companies listed on the Indonesian Stock Exchange. The data used is secondary data in the form of annual financial reports. Quantitative and qualitative data analysis methods using SPSS as a measuring tool. Data analysis technique that uses simultaneous tests and partial tests on the annual financial reports of consumer companies listed on the Indonesia Stock Exchange. The partial research results show that the variables capital structure and company size have a significant positive effect on company value and the variables profitability and dividend policy have no effect on company value, while simultaneous testing of the variables capital structure, company size, profitability and dividend policy has a significant effect on company value.